HAND SURGERY IN VIETNAM: DEVELOPMENT, CHALLENGES AND FUTURE DIRECTIONS - Van Thai, Nguyen; Văn Đoàn, Lê; Nghi Thanh Nhan, Le; Duong Phi, Nguyen (Journal of Health and Aging, 2025)
Hand surgery in Vietnam has evolved significantly, especially in cities like Ho Chi Minh City, Hanoi and Hue. Despite advancements, there remain challenges, including the lack of a unified national hand surgery society. This article highlights the contributions of key figures, advances and the future of the discipline in the country.
Keywords: hand surgery; microsurgery; development